6x+7+3x+1=

Simple and best practice solution for 6x+7+3x+1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+7+3x+1= equation:


Simplifying
6x + 7 + 3x + 1 = 0

Reorder the terms:
7 + 1 + 6x + 3x = 0

Combine like terms: 7 + 1 = 8
8 + 6x + 3x = 0

Combine like terms: 6x + 3x = 9x
8 + 9x = 0

Solving
8 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 9x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 9x = 0 + -8
9x = 0 + -8

Combine like terms: 0 + -8 = -8
9x = -8

Divide each side by '9'.
x = -0.8888888889

Simplifying
x = -0.8888888889

See similar equations:

| -4x+5=5-4x | | -3y+6=-4y+7 | | 7xy-xy+3xy= | | 4w-5+9w+2= | | -4+5=5-4x | | 20-x=10x-2 | | 3x-(2x+9)=4x-27 | | 87-5x=40x+22 | | x+(x+27)+(3x-24)=633 | | -14-4x=13-7x | | 4a^2-9b^2=0 | | 4m^2-9k^2=0 | | 11n-14= | | 2x-6=8x-24 | | x+7(4)=16 | | 12k+9=0 | | 9+6r-4=9r+14-2r | | m^4-4m^3+7m^2-4m+6=0 | | m^7+m^5= | | 6(6v+6)=1+6v | | 12-8x=39-15x | | 2t+11t=104 | | 6x+7=-199-8x | | 14=20-2x | | 30k+10=18k+22 | | 49*7= | | 9d+18=2d+18 | | 2t=-16 | | 18+6m=12m+48 | | 12*6.8= | | 15y+60=30y+120 | | 2.1*6= |

Equations solver categories